Hồ Thu Giang có nhầm lẫn rồi , sai bắt đầu từ dòng thứ 3:
\(\frac{1}{x}-\frac{1}{x+1}=\frac{1}{x}+\frac{1}{2011}\)
\(\frac{1}{x+1}=\frac{1}{x}-\left(\frac{1}{x}+\frac{1}{2011}\right)\)
\(\frac{1}{x+1}=\frac{1}{x}-\frac{1}{x}-\frac{1}{2011}\)
\(\frac{1}{x+1}=-\frac{1}{2011}\)
\(\Rightarrow x+1=-2011\)
\(\Rightarrow x=-2012\)
\(\frac{1}{x\left(x+1\right)}=\frac{1}{x}+\frac{1}{2011}\)
\(\frac{1}{x}-\frac{1}{x+1}=\frac{1}{x}+\frac{1}{2011}\)
\(\frac{1}{x+1}=\frac{1}{x}-\frac{1}{x}+\frac{1}{2011}\)
=> \(\frac{1}{x+1}=\frac{1}{2011}\)
=> x+1 = 2011
=> x = 2011 - 1
=> x = 2010
\(\Rightarrow\frac{1}{x\left(x+1\right)}-\frac{1}{x}=\frac{1}{2011}\)
\(\Rightarrow\frac{1}{x\left(x+1\right)}-\frac{x+1}{x\left(x+1\right)}=\frac{1}{2011}\)
\(\Rightarrow\frac{1-\left(x+1\right)}{x\left(x+1\right)}=\frac{1}{2011}\)
\(\Rightarrow\frac{-x}{x\left(x+1\right)}=\frac{1}{2011}\)
\(\Rightarrow\frac{-1}{x+1}=\frac{1}{2011}\Rightarrow x+1=-2011\)
\(\Rightarrow x=-2012\)
bạn ơi cho mình hỏi tại sao từ 1 / x(x+1) => 1/x-1/x+1 ?